Digging deeper into decision-making of Chinese long-haul outbound tourists: a two-stage preference estimation approach - Li, Chunxiao; McCabe, Scott; Li, Xiang (Elsevier, 2016)
Investigating and understanding tourists’ preferences is of great importance for both decision-making theories and destination marketing practice. In the current study we investigate the process of consideration-set formation together with conjoint analysis to estimate destination preferences of Chinese long-haul outbound tourists. Through the integration of choice-set and characteristic theories, this study explores how to obtain more comprehensive insights into destination choice processes. The findings show that preferences can be analysed effectively in a two-stage model, which can reveal detailed additional insights regarding tourists’ preferences towards destination attributes, thus contributing to marketing insight on destination choice and selection.